Kesan perubahan pinggir laut, vulnerabiliti dan adaptasi komuniti miskin di Kelantan, Malaysia / Nor Shahida Azali - Nor Shahida , Azali (2017)
Coastal areas is commonly defined as an interface or transition zone that connects the land and sea and it is also a very dynamic area. The interaction processes between the components of the subsystem and physical system within this zone, particularly those involving air, water, soil and biological systems resulted in the formation of coastal area. These occurring natural processes had changed the morphology of coastal area and its surrounding areas that is also known as coastal zone. Besides that, human activity also contributed to the changes occurring on the coastal zone, be it because of the area itself or human activity within the rural area. Apart from impacting the area’s morphology, these changes also threaten the coastal community particularly the poor community considering their source of livelihoods depend on the coastal zone that is subjected to changes due to environmental factors. Based on the rate of degradation percentage that occurs compared to the overall length of the coast, Kelantan is deemed as the state with the most severe changes to the coastal area. Therefore, this study was conducted to examine the changes on the coastal area from 1955 to 2011 and also to evaluate the vulnerability of the poor community considering that said community has low resilience and is more vulnerable to the threats from the changes. This study involved two major aspects namely the physical and human aspects. Physical aspects include the study related to coastal changes from 1955 to 2011 analyzed using the GIS (Geographic Information System) and RS (Remote Sensing) software as well as identifying the coastal zones, its morphology and occurring natural processes in order to produce a map of the coastal zone classification in the state of Kelantan. Meanwhile, the human aspects of the study evaluated the vulnerability index of the poor community in the coastal zone of Kelantan based on their perceptions towards four types of threats namely air, water, soil and biological systems. Besides that, these values also took into consideration the community’s existing adaptive capacity, internal and external indicators in their efforts to continue living in the coastal zone. Results from the overall vulnerability index shows that the poor community living in the coastal zone of Kelantan is threatened by the continuous changes on the coastal area caused by either aggradation or degradation process. To date, there are no appropriate management measures to reduce the level of degradation process in the coastal zones. The poor community had taken the initiative to implement immediate adaptation in case of upcoming threats to their residential areas. Apart from that, the government had also implemented both short and long term adaptation along the state of Kelantan’s coastal zone. However, the SWOC analysis (strength, weakness, opportunity and constraint) conducted at the end of this study also reveals many weaknesses and constraints as well as strengths and opportunities possessed by the poor community living in the coastal zone. In conclusion, the poor community in the coastal zone has to be made aware of the risk and threats posed by continuous coastal changes and the government also needs to strengthen the management measures in the coastal zone of Kelantan state.